Metagenomic characterization of indoor dust fungal associated with allergy and lung inflammation among school children - Mohd Isa, Khairul Nizam; Jalaludin, Juliana; Mohd Elias, Saliza; Lung Than, Leslie Thian; Jabbar, Mohammed Abdulrazzaq; Mohd Saudi, Ahmad Shakir; Norbäck, Dan; Hashim, Jamal Hisham; Hashim, Zailina (Elsevier, 2021)
The exposure of school children to indoor air pollutants has increased allergy and respiratory diseases. The objective of this study were to determine the toxicodynamic interaction of indoor pollutants exposure, biological and chemical with expression of adhesion molecules on eosinophil and neutrophil. A self-administered questionnaire, allergy skin test, and fractional exhaled nitric oxide (FeNO) analyser were used to collect information on health status, sensitization to allergens and respiratory inflammation, respectively among school children at age of 14 years. The sputum induced were analysed to determine the expression of CD11b, CD35, CD63 and CD66b on eosinophil and neutrophil by using flow cytometry technique. The particulate matter (PM2.5 and PM10), NO2, CO2, and formaldehyde, temperature, and relative humidity were measured inside the classrooms. The fungal DNA were extracted from settled dust collected from classrooms and evaluated using metagenomic techniques. We applied chemometric and regression in statistical analysis. A total of 1869 unique of operational taxonomic units (OTUs) of fungi were identified with dominated at genus level by Aspergillus (15.8%), Verrucoconiothyrium (5.5%), and Ganoderma (4.6%). Chemometric and regression results revealed that relative abundance of T. asahii were associated with down regulation of CD66b expressed on eosinophil, and elevation of FeNO levels in predicting asthmatic children with model accuracy of 63.6%. Meanwhile, upregulation of CD11b expressed on eosinophil were associated with relative abundance of A. clavatus and regulated by PM2.5. There were significant association of P. bandonii with upregulation of CD63 expressed on neutrophil and exposure to NO2. Our findings indicate that exposure to PM2.5, NO2, T. asahii, P.bandonii and A.clavatus are likely interrelated with upregulation of activation and degranulation markers on both eosinophil and neutrophil.